Pengaruh Konsentrasi Dan Lama Perendaman Dalam Larutan Sukrosa Terhadap Karakteristik Osmodehidrat Buah Buni (Antidesma bunius (L.) Spreng) - Yudhistira H.S, Dara Widya; Kartika Pratiwi, I Desak Putu; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPA, 2022)
Buni (Antidesma bunius (L.) Spreng) is one of the local berry fruit that can be used in the food processing sector and is an annual fruit (perennial). The objective of this research is to discover the concentration of sucrose and immersion time influence to osmodehydrate buni and determine the right treatment combination from the concentration of sucrose and immersion time to characteristics of osmodehydrate buni. This research used a Completely Randomized Design with two factors, variations of sucrose concentration (40%, 50%, 60%) and immersion time (1 hour, 2 hours, 3 hours). The treatment was repeated 2 times to obtain 18 experimental units. Data was analyzed with analysis of variance and if the treatment had a significant effect, then followed by the Duncan’s Multiple Range Test. The result showed that the osmosis solution concentration of 60% with immersion time of 3 hours produce the best characteristic of osmodehydrate buni with water content of 21.97%, weight loss of 64.36%, water reduction of 69.47%, the solid gain of 5.11%, the total sugar content of 29.18%, antioxidants activity of IC50 3304.73 ppm, the color is dark red and slightly liked, flavor slightly liked, the taste is slightly sour and liked, texture hard and slightly liked, overall acceptance slightly liked. Keywords: buni, immersion time, osmodehydrate, sucrose concentration